MIXED GERM CELL TERATOMATOUS TUMOUR OF TESTIS IN ADULTS: DIAGNOSTIC CHALLENGES FOR A HISTOPATHOLOGIST (case report) - Aden, D.; Shadan, M.; Khan, I. D.; Alam, F.; Naim, M.; Mohiyadheen, R.; Naim, E. (International Journal of Medicine and Medical Research, 2018)
Background. Testicular tumours account for approximately 1-2 % of the total cancer cases in the male population globally and show higher incidence in the younger male age group of up to 15 years. The majority (~98 %) of testicular tumours are observed to be of the germ-cell origin which can either be of seminomatous type or non-seminomatous type. The non-seminomatous germ cell neoplasm may be pure or of mixed subtype. Objective was to emphasize the rare case of mixed germ cell teratomatous tumour of testis in adult man. Methods. A mixed germ cell teratomatous tumour of testis comprising of yolk sac tumour and embryonal carcinoma in an adult Indian male is reported in the research. Results. A 45 year-old Indian male presented with enlargement of right testis which was found to be an encapsulated right testicular tumour on exploratory surgery which was followed by radical orchiectomy. Serum AFP and β-hCG levels were elevated to 380 ng/ml and 590 mg/ml respectively. Histopathology revealed a mixed germ cell teratomatous tumour of testis comprising of yolk sac tumour and embryonal carcinoma. Conclusions. In adults teratomas occur usually as a component of mixed germ cell tumours. However in the present case teratomatous embryoid yolk sac germ cell tumour of testis was observed in an Indian adult male. The prognosis of embryoid germ cell tumours of testis is generally poor. The possibility of this condition should always be considered in all cases that present with a testicular lump.